Institutes and Forms of Cooperation Between the Commonwealthand the States in Australia - E. B. Tsyrempilova (Сибирское юридическое обозрение, 2018)
This article explores the institutions and forms of interstate cooperation in Australia. The Author identifies four main forms of such cooperation: cooperation in lawmaking, consultation and coordination of activities, interstate agreements and the creation of interstate bodies. Analyzing each form, highlighting the strengths and weaknesses, the author draws attention to the fact that cooperative institutions may both enhance federalism or mask centralization.